Newly Designed Decellularized Scaffolds for Scaffold-based Gene Therapy from Elastic Cartilages via Supercritical Carbon Dioxide Fluid and Alkaline/ Protease Treatments - Huang, Ching-Cheng (Current Gene Therapy, 2022)
Background: Scaffold-based gene therapy provides a promising approach for tissue engineering, which was important and popular as it combined medical applications and engineering materials’ knowledge. Objective: The decellularization techniques were employed to remove the cellular components from porcine elastic cartilages, leaving a native decellularized Extracellular Matrix (dECM) composition and architecture integrity of largely insoluble collagen, elastin, and tightly bound glycosaminoglycans. For newly designed collagen scaffold samples, elastic cartilages were hydrolyzed by protease with different concentrations to gain state completely and clearly. Methods: An extraction process of Supercritical Carbon Dioxide (ScCO2) was used to remove cellular components from porcine elastic cartilage. The dECM scaffolds with collagen must be characterized by Fourier transform infrared spectroscopy(FTIR), Thermo-Gravimetric Analysis (TGA), and Scanning Electron Microscope (SEM). Results: The study provided a new treatment combined with supercritical carbon dioxide and alkaline/ protease to prepare dECM scaffolds with hole-scaffold microstructures and introduce into a potential application on osteochondral tissue engineering using scaffold-based gene therapy. The new process is simple and efficient. The pore-scaffold microstructures were observed in dECM scaffolds derived from porcine elastic cartilages. The Tdmax values of the resulting dECM scaffolds were observed at over 330°C. Conclusion: A series of new scaffolds were successfully obtained from porcine tissue by using ScCO2 and alkaline/enzyme treatments such as a mixing aqueous solution of NH4OH and papain. The dECM scaffolds with high thermal stability were obtained. The resulting scaffold with clean pore-scaffold microstructure could be a potential application for scaffold-based gene therapy.
Keywords: scaffold-based gene therapy